The Star, 09 Oktober 2007 - Lim, Chia Ying (Star Publications (Malaysia) Berhad, 2007)
For a public housing project (PPR) meant for low-income Malaysians relocated from squatter areas, the Damai Flats in Bandar Sunway has instead attained a very foreign face